Analisis Akad Jual Beli dalam Transaksi Mistery Box di Marketplace: Antara Hiburan dan Gharar (ketidakpastian) - M. Habib; Anisa Permata Dewi; Priskila Treka Zefatami; Bian Sandria Gihantoro; Naufal Rizky Refandhika; Nava Tiya Putri (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study examines in detail the phenomenon of online shopping using the Mystery Box scheme, currently popular on various e-commerce platforms. This phenomenon creates a conflict between innovative entertainment-based marketing strategies and compliance with Sharia principles in transactions. The approach used in this study is a descriptive qualitative method with a phenomenological and juridical-normative perspective. Although offering an entertaining experience, this practice raises serious issues related to the clarity of the transaction object (ma’qud ’alaih) because it contains gharar fahish or excessive uncertainty that negatively impacts consumers. This contradicts the principle of transparency stipulated in the JPH Law and Government Regulation No. 42 of 2024, which guarantees consumers’ right to obtain accurate information. From a theological perspective, the speculative element similar to gambling (maysir) in the Mystery Box is prohibited according to Surah Al-Baqarah verse 188:وَلَا تَأْكُلُوا أَمْوَالَكُمْ بَيْنَكُمْ بِالْبَاطِلِ وَتُدْلُوا بِهَا إِلَى الْحُكَّامِ لِتَأْكُلُوا فَرِيقًا مِنْ أَمْوَالِ النَّاسِ بِالْإِثْمِ وَأَنْتُمْ تَعْلَمُون “And do not devour your neighbor’s wealth unjustly..." As a solution, transactions can be legitimate if the element of ignorance is reduced through transparency regarding the minimum value of goods equal to the price paid. The study concluded that the integrity of the digital market must be maintained through strict platform regulation and consumer education so that every transaction remains based on the principle of ’antaradin (mutual consent) and the values ​​of Sharia justice.